Training on Tunnel Technology to Increase Salt Production in Jepara Regency - Prihatmoko, Dias; Mustofa, Arif; Sarwido, Sarwido; Wijaya, Akhmad Pandhu (LP2M INSURI Ponorogo, 2024)
Rainwater is one of the factors that can affect salt production in Jepara Regency. Salt tunnel technology can retain rainwater so that salt farmers can produce salt even during the rainy season. However, salt farmers have not yet fully utilized this technology. So that assistance is needed to them about the application of salt tunnel technology. This program is conducted to increase the knowledge and skills of salt farmers about salt tunnel technology. The community service partner is UKM Rumah Garam in Surodadi Village, Kedung District, Jepara Regency. The activity was carried out in August 2024. The flow of implementing activities includes preparation, provision of tools and materials, implementation of training, partner assistance and evaluation. The training was attended by partner members with training material on Sustainable Salt Production Technology. The next stage is the field practice of making salt tunnel construction in the salt field owned by one of the participants. The construction is made of bamboo and the soil is coated with geoisolator while the cover uses UV plastic. The community service activity was able to increase the knowledge and skills of the participants about salt tunnel technology which is expected to increase the amount of salt production.